Investigating the pragmatic meaning of the smiley emoticon on Whatsapp groups: a cyberpragmatics perspective - Rahardi, R. Kunjana (BAHASTRA, 2022)
This study aims to describe the pragmatic meanings contained in smiley emoticons in cyberpragmatics research. Sources of data were social media, especially from Whattsup taken in a certain period around the time of this research. The source of substantive data was the excerpts of speech in which there were certain expressive meanings that were emotive in nature. The object of this research was the pragmatic meaning of emoticons in speech. The data of this research were emoticons in speech that describe a specific purpose. The data were collected by using the reading method and note taking technique. The data were followed up with a data classification step and a data typification step. Prior to analysis, the data were validated by applying expert triangulation and theory triangulation. The analytical method used was the extralingual equivalent analysis method. The steps used in the analysis of research data were described as follows: selection, classification, and interpretation. The results of the research were presented as follows: (1) Emoticons show the intention of satisfaction and happiness, (2) Emoticons show the intention to tease with praise, (3) Emoticons show the intention of being overly excited, (4) Emoticons show the intention of worrying, (5) Emoticons show the meaning of gratitude is full of joy, (6) Emoticons show the intention of gratitude with a smile and pride, (7) Emoticons show enthusiasm and a feeling of joyful joy.